2022
DOI: 10.1242/jeb.243872
|View full text |Cite
|
Sign up to set email alerts
|

An accelerometer-derived ballistocardiogram method for detecting heart rate in free-ranging marine mammals

Abstract: Physio-logging methods, which use animal-borne devices to record physiological variables, are entering a new era driven by advances in sensor development. However, existing datasets collected with traditional bio-loggers, such as accelerometers, still contain untapped eco-physiological information. Here we present a computational method for extracting heartrate from high-resolution accelerometer data using a ballistocardiogram. We validated our method with simultaneous accelerometer-electrocardiogram tag deplo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Unlike fields such as genomics, biologging does not yet have a central data repository or standardization practice [23, 28,29]. Data-driven questions and global collaborations can enable researchers to reuse or re-analyze data for new discoveries [10,31,44,45], reducing the number of animals that experience the impacts of carrying an instrument. 2h.…”
Section: B Carefully Choose Sample Sizesmentioning
confidence: 99%
“…Unlike fields such as genomics, biologging does not yet have a central data repository or standardization practice [23, 28,29]. Data-driven questions and global collaborations can enable researchers to reuse or re-analyze data for new discoveries [10,31,44,45], reducing the number of animals that experience the impacts of carrying an instrument. 2h.…”
Section: B Carefully Choose Sample Sizesmentioning
confidence: 99%
“…Moreover, the LiDAR-based breath measurement could capture the relative pattern transition, like invasive sensors (Czapanskiy et al, 2022). An analysis of the video data suggested that the lion's breathing was initially shallow and irregular between 4 and 5 0.310m 0.297m seconds, stabilizing into a more consistent and deep breathing pattern afterward.…”
Section: Fine Scale Deformation Monitoringmentioning
confidence: 99%
“…The primary component of the BCG, a complex of three distinctive, energetic deflections denoted I, J, and K, is associated with systole (Rappaport, 1956;Inan et al, 2015;Tavakolian et al, 2022). Recent BCG measurement developments aim for ubiquitous longitudinal cardiovascular monitoring, for example, heart rate (HR) monitoring (Jung et al, 2021;Czapanskiy et al, 2022). Amplitude and peak width of the IJK components have been associated with stroke volume (SV) and ejection duration (Starr, 1955;Inan et al, 2015;2009b;Ashouri et al, 2016;Quesada et al, 2021).…”
Section: Introductionmentioning
confidence: 99%